Dukungan Sosial dan Resiliensi Remaja yang Mengalami Kesulitan Hidup: Systematic Literature Review Using Big Data Analysis - Auliya, Naila Putri Dita; Nur Eva (Jurnal Psikologi, 2025)
Adolescence is a transition period from childhood to adulthood. They will begin to form their identity and face various challenges that have the potential to affect their mental and emotional health. In this journey, there are still many teenagers who have to face significant life difficulties, such as family problems, academic difficulties, disabilities, or even emotional trauma. Adolescents who experience difficulties in life need to have resilience skills to be able to survive and face the problems they face. Social support makes individuals more resilient in stressful situations and equips individuals with resources to bounce back from difficult circumstances. The design used in this study is a systematic literature review which consists of several steps, namely (1) literature collection, (2) selection of relevant literature, (3) literature review using the focus of content analysis, (4) withdrawal of review results, and (5) discussion of review results. Researchers use two applications to search and analyze large amounts of data (big data). Based on the results of a review of 200 research articles, 7 articles were selected that are most relevant to this study. Social support has a significant influence in increasing the resilience of adolescents who experience difficulties in life. However, social support is not the main factor in determining resilience in adolescents who experience difficulties in life.